A human B‐cell interactome identifies MYB and FOXM1 as master regulators of proliferation in germinal centers - Celine Lefebvre; Presha Rajbhandari; Mariano J Alvarez; Pradeep Bandaru; Wei Keat Lim; Mai Sato; Kai Wang; Pavel Sumazin; Manjunath Kustagi; Brygida C Bisikirska; Katia Basso; Pedro Beltrao; et al. (Molecular Systems Biology)
Abstract Assembly of a transcriptional and post‐translational molecular interaction network in B cells, the human B‐cell interactome (HBCI), reveals a hierarchical, transcriptional control module, where MYB and FOXM1 act as synergistic master regulators of proliferation in the germinal center (GC). Eighty percent of genes jointly regulated by these transcription factors are activated in the GC, including those encoding proteins in a complex regulating DNA pre‐replication, replication, and mitosis. These results indicate that the HBCI analysis can be used for the identification of determinants of major human cell phenotypes and provides a paradigm of general applicability to normal and pathologic tissues.